A Mixed Method Study On Social Sustainability Consideration By Public Sector Organizations During Infrastructure Procurement - Diba, N.M.J.; Awuzie, B.O.; Aigbavboa, C.O.; Haupt, T.C. (Journal of Construction, 2019)
PURPOSE Although adequate consideration is being accorded to economic and environmental aspects of sustainable development (SD) during infrastructure procurement, the opposite seems to be the case with social sustainability aspects (SSA). This study elicits the perspectives of procurement officials working in public sector infrastructure client organizations (ICOs) as it concerns the factors influencing the incorporation of SSA during infrastructure procurement. RESEARCH METHOD A mixed method research design was adopted. Qualitative data was sourced from purposively selected interviewees whilst quantitative data were obtained from respondents within selected ICOs. Qualitative data were analysed thematically and, descriptive statistics was deployed in the analysis of the quantitative data. FINDINGS Results indicate a lack of awareness and a knowledge gap concerning social sustainability aspects. Furthermore, the results highlight the influence of the levels of understanding within the ICOs on the degree of incorporation of SSA aspects during infrastructure procurement. It is expected that these findings will contribute to the development of awareness and, subsequent incorporation of SSA by relevant stakeholders during infrastructure procurement in the Free State Province. VALUE FOR AUTHORS The findings reveal how procurement personnel of infrastructure client organizations view the concept of sustainability and factors, which influence the approach of various infrastructure client organizations in engaging with the incorporation of SSA during the procurement processes of the infrastructure projects.
Published Article
Keywords: Procurement; Sustainable Infrastructure Development; Procurement Methods; Public Procurement; Social Sustainability Aspects